2003
DOI: 10.1029/2002tc001484
|View full text |Cite
|
Sign up to set email alerts
|

Accretion leading to collision and the Permian Solonker suture, Inner Mongolia, China: Termination of the central Asian orogenic belt

Abstract: The Solonker suture records the termination of the central Asian Orogenic Belt (CAOB). However, tectonic development of the Solonker suture is poorly understood. We report new field data for the Ondor Sum melange in the Ulan valley, and present a new evaluation of the orogenic belt extending from the southern Mongolia cratonic boundary to the north China craton within the context of a new geological framework and tectonic model, which incorporates relevant data from the literature. The southern accretionary zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
1,215
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,701 publications
(1,233 citation statements)
references
References 39 publications
17
1,215
0
1
Order By: Relevance
“…10), which is consistent with their post-collisional characteristics. It is also consistent with the previous studies on the Bayan Obo REE deposit (Ling et al, 2013), i.e., plate subduction during the closure of the Palaeo-Asian Ocean started in the Neoproterozoic (Khain et al, 2003) and lasted until the Carboniferous/Permian (Xiao et al, 2003).…”
Section: The Geochemical Characteristics Of Permian-triassic Granitoisupporting
confidence: 93%
“…10), which is consistent with their post-collisional characteristics. It is also consistent with the previous studies on the Bayan Obo REE deposit (Ling et al, 2013), i.e., plate subduction during the closure of the Palaeo-Asian Ocean started in the Neoproterozoic (Khain et al, 2003) and lasted until the Carboniferous/Permian (Xiao et al, 2003).…”
Section: The Geochemical Characteristics Of Permian-triassic Granitoisupporting
confidence: 93%
“…further suggested that the Late Triassic-Late Jurassic collision between the southern Kunlun and Northern Qiangtang active margins possibly generated a collisional complex including two forearc basins and their accretionary complexes. This kind of collision is typical in accretionary orogens, which can be found in modern examples like the Molucca Sea (Hall, 2002) and their ancient counterparts such as Inner Mongolia (Xiao et al, 2003), the Kelameili suture between the Northern Tianshan arcs and the East Junggar arcs (Xiao et al, 2004), and the Mongol-Okhotsk suture (Tomurtogoo et al, 2005). Therefore, we suggest that the northern Hohxil high-Mg andesites and dacite suites, occurring just south of the Anyimaqen-Kunlun-Muztagh suture, were most likely generated in a forearc setting (Fig.…”
Section: Tectonic Implicationsmentioning
confidence: 93%
“…1a). Since the Late Paleozoic, it has undergone long-term plate subduction and continent-arc and/or microcontinent-continent collisions before the ultimate collision between the North China-Mongolian Block and the Siberian Craton (Zhao et al, 1990(Zhao et al, , 1994Sengör et al, 1993;Van der Voo et al, 1999;Xiao et al, 2003;Jia et al, 2004;Li, 2006). Consequently, widespread Phanerozoic granitoids were formed in NE China and along the north margin of North China Block (Wu et al, 2000(Wu et al, , 2003(Wu et al, , 2005Jahn et al, 2001;Sun et al, 2001;Meng, 2003;Hong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%